1995
DOI: 10.3109/07853899509031970
|View full text |Cite
|
Sign up to set email alerts
|

New Developments in Patient-controlled Postoperative Analgesia

Abstract: Patient-controlled analgesia (PCA) is a newer technique for pain management. Patients are allowed to self-administer small analgesic bolus doses into a running intravenous infusion, intramuscularly, subcutaneously or even into the epidural space. Demands are usually controlled by computer-driven infusion pumps, but can also be delivered by disposable devices. Clinical experience demonstrates that individual variability in pain sensitivity and analgesic needs are of utmost importance. In contrast to earlier exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 96 publications
0
7
0
1
Order By: Relevance
“…In the present study no differences were found in the VRS or VAS scores on postoperative pain at rest or swallowing. According to our results, it can be assumed that differences in oxycodone consumption indicate the analgesic efficacy of the study drugs (9).…”
Section: Discussionmentioning
confidence: 77%
“…In the present study no differences were found in the VRS or VAS scores on postoperative pain at rest or swallowing. According to our results, it can be assumed that differences in oxycodone consumption indicate the analgesic efficacy of the study drugs (9).…”
Section: Discussionmentioning
confidence: 77%
“…4 Analgesic delivery systems that are controlled by the patient (patient-controlled analgesia or PCA) provide better pain control than standard modes of delivery because they allow continuous patient access to pain medication within predetermined limits. 1 Such PCA systems are both efficacious and well accepted. The PCA systems are fully computerized portable syringe pumps with a reservoir for the drug solution.…”
Section: Introductionmentioning
confidence: 98%
“…Für Alfentanil, Buprenorphin, Fentanyl, Metamizol, l-Methadon, Morphin, Nalbuphin, Nefopam, Pentazocin, Pethidin, Piritramid und Sufentanil sind entsprechende Befunde verfügbar [17]. Vornehmlich ging es darum, unter einheitlichen Bedingungen die analgetische Potenz, Ver-träglichkeit und Patientenakzeptanz zu bestimmen.…”
Section: Zusammenfassungunclassified